What did the biblical writers know and when did they know it? what archaeology can tell us about the reality of ancient Israel - Dever, William G. (Grand Rapdis, MI Eerdmans, 2001)
Includes bibliographical references and indexes.
Keywords: Bible. O.T. -- history of Biblical events; Jews -- history